Multicultural folk tales - Jeffries, David; Fullam, Sue Mead; Vasconcelles, Keith; Teacher Created Materials, Inc. (Huntington Beach, CA : Teacher Created Materials, Inc., 1992)
Reproducible pages designed to teach children about folk tales of the world, centered on the African folk tale Mufaros' beautiful daughters and the Eskimo folk tale Song of Sedna.
"Reproducible--Intermediate."--Cover.
Includes bibliographical references (p. 79).
Keywords: Folk literature -- Study and teaching (Primary); Language experience approach in education; Language arts -- Correlation with content subjects